Alone In The Dark - Rose, Karen (London Headline Books, 2015)
Homicide detective Scarlett Bishop has seen enough bad guys slip through the cracks and innocent victims go unavenged to know that good doesn't always prevail. So far she's been able to lock away her rage and her vigilante fantasies. That lock is about to break.
Keywords: Human trafficking -- Veterans -- Police